2021
DOI: 10.3390/rs13193994
|View full text |Cite
|
Sign up to set email alerts
|

Paddy Rice Mapping in Thailand Using Time-Series Sentinel-1 Data and Deep Learning Model

Abstract: The elimination of hunger is the top concern for developing countries and is the key to maintain national stability and security. Paddy rice occupies an essential status in food supply, whose accurate monitoring is of great importance for human sustainable development. As one of the most important paddy rice production countries in the world, Thailand has a favorable hot and humid climate for paddy rice growing, but the growth patterns of paddy rice are too complicated to construct promising growth models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, this data is based on the farmer's decleration as stated above. It is known that mostly declared statements do not represent real production areas (Sitokonstantinou et al, 2021;Xu et al, 2021). As can be seen here, 27.69 km 2 more paddy rice cultivation was calculated in Ipsala district in 2021 than declared.…”
Section: Classification Mapsmentioning
confidence: 85%
“…However, this data is based on the farmer's decleration as stated above. It is known that mostly declared statements do not represent real production areas (Sitokonstantinou et al, 2021;Xu et al, 2021). As can be seen here, 27.69 km 2 more paddy rice cultivation was calculated in Ipsala district in 2021 than declared.…”
Section: Classification Mapsmentioning
confidence: 85%
“…Rice is ingested by more than 50% of the Earth's inhabitants, and rice paddies cover more than 10% of the total cropland worldwide. On a global scale, rice is the main contributor among plant-based sources to the discharge of greenhouse gases [1]. Precise and current data on rice production are of paramount importance in achieving food and environmental objectives and safeguarding access to water.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the two-satellite constellation of Sentinel-2 enhances its temporal resolution to an impressive interval of 5 days. Numerous research efforts have presented the effective utilization of S1 data for the mapping of rice fields in different nations, such as Vietnam [9][10], China [11][12][13][14], the USA and Spain [15], India [16][17], the Mediterranean region [18], Iran [19], Bangladesh [20], South Korea [21], Indonesia and Malaysia [22], Philippines [23], Thailand [1,24], and Myanmar [25]. Simultaneously, S2 has also proven its efficiency in accurately mapping rice fields in the context of Egypt [26] and China [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Kussul et al used 19 scenes of Sentinel-1A and Landsat-8 data and a shallow CNN for crop classification in Ukraine, which showed that the CNN architecture outperformed the multilayer perceptron architecture, resulting in accuracies above 85% for major crops [35]. Xu et al extracted temporal statistical features based on 758 scenes of Sentinel-1 images from late 2018 to 2019, covering Thailand, and fed the features into a U-Net model with a fully connected conditional random field to generate an annual rice map [36]. Experimental results showed that the method achieved the best overall performance compared to the SVM classifier and the feature selection strategy-based U-Net model, and the overall accuracy reached 91%.…”
Section: Introductionmentioning
confidence: 99%